Plato, Heraclitus and Dante on ambiguity. Some notes to Prof. Smith's paper (text in English) (Nóema, 2014)
The purpose of this note is to discuss some aspects of Prof. Smith's paper about Virgil and the ambiguity. The note is divided into three parts: a) a discussion about the ambiguity of the empirical things in Plato; b) a reconsideration of Heraclitus' fragment 26 DK, in the light of some observation by H.G. Gadamer; c) a short comparison between Virgil's Polydorus and Dante's Pier Delle Vigne about the uncanny nature of their otherworldly transfiguration.
Keywords: Ambiguity; Plato; Heraclitus; Dante; Pier Delle Vigne